INVOLVEMENT OF REGION OF SPINE AND TYPE OF FRACTURES WITH RESPECTIVE MODE OF TRAUMA - UDDIN, MM; ZULQARNAIN, .; YAQOOB, U; ABBAS, H; HALIM, SA; HAQ, MZU (Biological and Clinical Sciences Research Journal, 2024)
Spinal injuries are complex and often result from traumatic events such as falls, road traffic accidents, and impacts from heavy objects. Proper assessment of the injured spinal region, classification of the injury type, and evaluation of neurological impairment are critical for determining prognosis and guiding management. Objective: This study aims to assess the correlation between spinal regions involved and the mode of trauma, while also comparing the severity and prognosis of spinal injuries using the AO Spine Trauma Classification, Subaxial Cervical Spine Injury Classification (SLICS), Thoracolumbar Injury Classification and Severity Score (TLICS), and American Spinal Injury Association (ASIA) grading systems. Methods: After the ethical approval from the institutional review board, this cross-sectional was conducted at Shaheed Mohtarma Benazir Bhutto Institute of Trauma (SMBBIT), Karachi from 1st June 2022 to 31st December 2023 . Through non-probability consecutive sampling 100 patients aged 15-60 years, both gender, who had a spinal injury due to any sort of trauma (RTA, fall, or impact by an object, etc) were included in the present study. Results: The most common cause of spinal trauma was falls from height, accounting for 59% of cases, followed by road traffic accidents (22%), falls from heavy objects (16%), and assaults (3%) (Table 1). Lumbar spine fractures were the most prevalent, occurring in 41% of participants, followed by thoracic fractures (34%) and cervical fractures (25%). In terms of fracture classification, the AO-spine system identified 51% of subaxial cervical spine fractures as Type A, while thoracolumbar spine fractures were predominantly Type B (58%).SLICS classification revealed that 70% of fractures were compressions, and 51% of patients had nerve root injurie. The ASIA scale revealed 12% of patients had complete motor and sensory loss (Grade A), while 30% retained normal function (Grade E). Conclusion: This study supports the earlier works where spinal injuries are complex trauma and require more elaborate assessment and classification systems for patient management.